IMPLEMENTASI MANAJEMEN KEUANGAN SYARIAH PADA UMKM UDANG KETAK DI KECAMATAN NIPAH PANJANG - Pratiwi Putri, Indah; Agustin Nengsih, Titin; Embun Baining, Mellya (Program Studi Manajemen Keuangan Syariah, 2023)
ABSTRACT This thesis is motivated by the importance of implementing Islamic Financial Management for MSMEs so that they can manage their money or assets in accordance with Islamic Sharia. When the development of MSMEs in Indonesia was tested by the emergence of the Covid-19 outbreak in the midst of Indonesian society. The Covid-19 pandemic also had an impact on the Ketak Shrimp MSMEs in Nipah Panjang District which caused a decrease in income and sales levels. MSMEs still face obstacles in increasing capital, both for working capital and for investment capital. MSMEs face various obstacles or problems that can be caused by low education, lack of understanding of information technology and obstacles in preparing financial reports. Internal constraints that are very often experienced by SMEs are limited human resources. This study aims to find out how the implementation of Islamic financial management in the shrimp ketak business and to find out what obstacles or obstacles faced by the shrimp ketak SMEs to implement the implementation of Islamic financial management. In this study using a qualitative approach. Sources of data used are primary and secondary data sources. While the data collection method is by conducting observations, interviews, documentation and drawing conclusions. The results of the study indicate that MSMEs have problems in their operations, especially in Islamic Financial Management. Based on the results of interviews, the inhibiting factors for the implementation of Islamic financial management can be seen from the absence of financial reports and the limited knowledge of business owners about the technology that is currently developing. MSMEs should be able to develop themselves with Islamic financial management, from the process of obtaining funds, using funds that should be planned so that they can be useful for the future and also the process of managing assets that should have special funds for their operations so that they are maintained and can be durable for the future. . Keywords: Islamic Financial Management, MSMEs, Financial Reports, HR